(3JChjdGJ hfbhd Yf GdUhajIs - (3SYO GdOjf eMeO Hf GdeDjO CHj HcQ Hf CHj GdMSf Hf eMeO GdMehj,J (B650 (3g` s
(3ChdgG (B:s
(3gPg cdeGJ PhbjI EYdehG jG ENhGf GdJLQjO Gf aGFOI GdJLQjO GdYhO Edi GdhWf GdCUdi hGdGJUGd Edi YGde GdYbdi s
(3BNQgG (B:s
(3hWdYJ ef WGdY dSGfg GTYI eYGQag hGfhGQ HjGfg aGVGJ fhGXQ NhGWQ ENhGfg aGfJXehG ai Sdc YQaGfg hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B70s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs